Why have China's military deployments overseas remained low despite possessing the capabilities to deploy troops abroad? - Seow, Ian Cheng Wei (Nanyang Technological University, 2023)
China’s re-emergence as a military power has generated debates within existing International Relations (IR) theories about China’s military deployments overseas. Offensive realism opine that China will deploy troops abroad to challenge the US’ hegemony in Asia, while social constructivism argue that China’s military deployments are driven by its changing identities and interactions with the international community. However, this thesis observes that existing IR theories are inadequate in explaining why China’s military deployments overseas have remained low despite its improved capabilities to deploy troops abroad and expanding overseas interests. To fill this research gap, this thesis uses quantitative and qualitative analyses of China’s Defence White Papers to examine how China’s strategic culture influences its low military deployments abroad. This thesis argues that China’s longstanding security concerns about its periphery is the most important reason influencing its low military deployments overseas as it requires a large military to deter external threats to its security.